Efficacy of a Novel Rigenase® and Polyhexanide (Fitostimoline® Septagel) Hydrogel Device for the Treatment of Vulvovaginitis Symptoms: Cross-Sectional Analysis of a National Survey and Prospective Observational Study - Gaetano Riemma; Giampaolo Mainini; David Lukanović; Gaetano Scalzone; Lucia Sandullo; Maria Teresa Schettino; Maria Giovanna Vastarella; Mattia Dominoni; Gorizio Pieretti; Pasquale De Franciscis; Mario Passaro; Marco Torella (Medicina, 2023)
Background and Objectives: Signs and symptoms of vulvovaginitis, especially when recurrent, have a significant impact on a woman’s quality of life. The aim of this study was to survey gynecologists about their habits regarding the treatments of the pathology and to evaluate the efficacy of a novel vaginal hydrogel composed of wheat extracts and polyhexanide aimed at reducing vulvovaginitis symptomatology. Materials and Methods: A cross-sectional analysis of a national survey using 155 Italian gynecologists and a prospective, open-label, observational study were carried out in 75 outpatient clinics across Italy. Pre- and postmenopausal women with suspicion of vulvovaginitis due to at least four of the following symptoms (leucoxanthorrhea, bad odor from genitalia, vulvovaginal dryness, petechiae, burning, and pruritus) while waiting for microbiological swab analysis were included and treated with one hydrogel application every 3 days for 1 week. Primary endpoint was the complete resolution of symptomatology. Results: The pre-study survey reported that, for most clinicians, local or oral treatment (65.7% and 82.8%, respectively) with antibiotics or antifungals is used very often. Therefore, we proceeded to carry out an observational study. Overall, 615 (362 of fertile age and 253 in postmenopause) women were included in this study. At the 28th follow-up examination, complete resolution of symptomatology was achieved in 578/615 (94.1%; p < 0.001) within 12.72 ± 6.55 and 13.22 ± 6.33 days for those of fertile age and in postmenopause, respectively (p = 0.342). All of the evaluated symptoms were significantly reduced after treatment (p = 0.001) without differences according to the patient’s menopausal status. A slightly significant reduction in Gardnerella Vaginalis (p = 0.040) and Candida Albicans (p = 0.049) was found after treatment. No patient reported side effects, adverse reactions, or discontinued therapy. Conclusions: This pilot study showed that a hydrogel based on Rigenase® (wheat extract) and polyhexanide could be a promising treatment for the relief of vulvovaginitis symptoms. However, these results are limited by the absence of a control group. Additional comparative and randomized controlled trials between the hydrogel and other non-antibiotic devices as well as local antibiotic therapy should be performed to increase the validity of the findings.